Three‐dimensional distribution of a major desert dust outbreak over East Asia in March 2008 derived from IASI satellite observations. Issue 14 (29th July 2015) - Cuesta, Juan; Eremenko, Maxim; Flamant, Cyrille; Dufour, Gaëlle; Laurent, Benoît; Bergametti, Gilles; Höpfner, Michael; Orphal, Johannes; Zhou, Daniel
Abstract We describe the daily evolution of the three‐dimensional (3D) structure of a major dust outbreak initiated by an extratropical cyclone over East Asia in early March 2008, using new aerosol retrievals derived from satellite observations of IASI (Infrared Atmospheric Sounding Interferometer). A novel auto‐adaptive Tikhonov‐Phillips‐type approach called AEROIASI is used to retrieve vertical profiles of dust extinction coefficient at 10 µm for most cloud‐free IASI pixels, both over land and ocean. The dust vertical distribution derived from AEROIASI is shown to agree remarkably well with along‐track transects of CALIOP spaceborne lidar vertical profiles (mean biases less than 110 m, correlation of 0.95, and precision of 260 m for mean altitudes of the dust layers). AEROIASI allows the daily characterization of the 3D transport pathways across East Asia of two dust plumes originating from the Gobi and North Chinese deserts. From AEROIASI retrievals, we provide evidence that (i) both dust plumes are transported over the Beijing region and the Yellow Sea as elevated layers above a shallow boundary layer, (ii) as they progress eastward, the dust layers are lifted up by the ascending motions near the core of the extratropical cyclone, and (iii) when being transported over the warm waters of the Japan Sea, turbulent mixing in the deep marine boundary layer leads to high dust concentrations down to the surface. AEROIASI observations and model simulations also show that the progression of the dust plumes across East Asia is tightly related to the advancing cold front of the extratropical cyclone.